Perspective Supervision in Islam - Iwan Setiawan; Agus Gunawan; Enung Nugraha (MultiTech Publisher, 2023)
In the Islamic context, educational supervision has high relevance, as education is considered one of the important aspects in the development of spiritually and academically balanced individuals. This article discusses educational supervision from an Islamic perspective and explains the principles, objectives, and methods of supervision that are in accordance with Islamic values. Theoretical Studies: This article refers to various sources of theory in Islam that are relevant to educational supervision. Some of the concepts that are in focus are